2020
DOI: 10.1212/nxi.0000000000000845
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring B cell depletion therapy in MS according to memory B cell monitoring

Abstract: ObjectiveWe wanted to evaluate efficacy on inflammatory parameters of rituximab (RTX)-personalized reinfusion scheme using a memory B cell–based treatment regimen.MethodsThis is a prospective, uncontrolled, open-label study including patients with MS treated with RTX in 2 Italian MS units. All patients were treated with RTX induction, followed by maintenance infusion at the dosage of 375 mg/m2, according to memory B cell repopulation (0.05% of peripheral-blood mononuclear cells [PBMCs] for the first 2 years, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 9 publications
1
29
0
Order By: Relevance
“…( 5 ) This is supported by the results of the recently published study which showed that the memory B cell–based rituximab reinfusion protocol is able to reduce the mean number of rituximab reinfusions with persistent reduction of disease activity. ( 9 ) Similar findings are observed in the present study, where we have not found increased occurrence of relapses despite higher repopulation of B cells.…”
Section: Discussionsupporting
confidence: 93%
“…( 5 ) This is supported by the results of the recently published study which showed that the memory B cell–based rituximab reinfusion protocol is able to reduce the mean number of rituximab reinfusions with persistent reduction of disease activity. ( 9 ) Similar findings are observed in the present study, where we have not found increased occurrence of relapses despite higher repopulation of B cells.…”
Section: Discussionsupporting
confidence: 93%
“…For this reason, cells within the memory B cell subsets appear to be important targets for disease control, and their depletion and slow repopulation may, in part, account for the long-term disease control seen from short-term treatment cycles with alemtuzumab, cladribine, ocrelizumab and rituximab [2,3,9,10]. Using rituximab to deplete repopulating memory B cells when they reach predefined levels can maintain clinical remission while reducing the frequency of infusions in RA, NMO, MS and other conditions [3,[11][12][13]. Translating this knowledge may help to improve the benefit : risk balance of ocrelizumab [9].…”
Section: Introductionmentioning
confidence: 99%
“…This strategy is currently being tested in natalizumab with a view to reduce the risk of developing progressive multifocal leucoencephalopathy (17). Furthermore, preliminary studies with rituximab may suggest that dosing to memory B cell population kinetics can reduce dosing frequency whilst maintaining efficacy (18) Despite policies to make trial-data available, trial-information presented at major international conferences are not always followed by peer-reviewed publications (5,19). Therefore, information cannot easily be searched or interrogated by internet engines and fails to become common knowledge and perhaps allows people to be unwittingly exposed to unnecessary safety issues (19).…”
Section: Introductionmentioning
confidence: 99%